P131 Effectiveness and safety of vedolizumab maintenance therapy for inflammatory bowel disease: findings from a Belgian registry. (25th January 2019) - Louis, E; Muls, V; Bossuyt, P; Colard, A; Nakad, A; Baert, D; Mana, F; Caenepeel, P; Vanden Branden, S; Vermeire, S; D'Heygere, F; Strubbe, B; et al.
Abstract: Background: Clinical trials have demonstrated the efficacy and safety of vedolizumab (VDZ) as maintenance therapy for Crohn's disease (CD) and ulcerative colitis (UC). This report presents outcome data for VDZ maintenance therapy in real life practice in Belgium. Methods: The Belgium VDZ Registry includes 202 VDZ-treated adult patients from 19 Belgian centres. Inclusion criteria were on-going VDZ therapy started 15+ days prior to recruitment and patient not in a clinical trial or VDZ PASS study. This interim analysis presents safety data for the all 202 registry participants, and clinical remission rates on the subset of 156 participants with at least one 6-monthly investigator update on clinical management and outcomes. Clinical remission was defined as Harvey–Bradshaw Index <5 or partial Mayo score < 3 with no sub-score >1. Patients who discontinued VDZ were considered not in remission from that point forwards. An imputation analysis was included to account for missing disease activity scores, where a missing activity score was assumed not in remission, thereby giving a minimum imputation estimate. Results: The characteristics of the 202 participants were 52% female, 66% had CD, predominantly ileal or ileocolonic CD, and 34% had UC, predominantly left-sided UC. Median age at onset of IBD was 28 years, and median duration of IBD prior to starting VDZ was 10 years. At recruitment, median length of on-going VDZ therapy was 11 months, and 63% of UC and 60% of CD patients were in remission. Median duration of follow-up in the outcomes subset was 11 months (range 4–18 months). Clinical remission rates are shown below. The corresponding rates of corticosteroid-free clinical remission were 30–40% for both CD and UC. All reported serious adverse events (SAEs) and non-serious AEs were considered un-related to VDZ therapy. Thirty-four patients (16.8%) had a SAE, the most frequent being worsening of CD/UC (4.0%) and small intestine obstruction (1.5%). Eighty patients (39.6%) had a non-serious AE, the most frequent being constipation (2.5%), gastroenteritis (2.0%), nasopharyngitis (2.0%), and upper respiratory tract infection (2%). There were no reports of hepatic injury, infusion-related reactions, hypersensitivity or opportunistic infection. Conclusions: These real-life data collected from 19 gastroenterology centres across Belgium demonstrate sustained clinical benefit with up to 36 months of VDZ maintenance therapy in everyday clinical practice.